EFFECTS OF BETA -1,3/1,6 GLUCAN ON SURVIVAL AND VIBRIO ALGINOL YTICUS RESISTANCE OF AMPHIPRION FRENATUS (BREVOORT, 1856) - Thuy, Nguyen Thi Thanh; Yen, Nguyen Hoang (Vietnam Journal of Marine Science and Technology, 2009)
Three day old Tomato Clown fish (Amphipri011 frenatus) were reared in an open water system and daily fed on nauplii Artemia. Every 5 days, treated fish were bathed with varying concentrations of 8.4, 184 and 920mg/L. separately. After 25 days of treatment, survival and total protein offish was analyzed. Then, all the fish were bathed with Vibrio alginolyticus solution at initial density of 107 cell/mL. The bacterial resistance of the fish was based on the cumulative mortalities, relative percent survival (RPS) and survivals after 3 weeks of challenging. The results showed that, in normal condition there was no significant difference in the survivals and total protein of the fish among the treatments and control. However, after challenging with Vibrio alginolyticus, the survivals of the bathed fish significantly increased (84-100%) compared to the control (75%).